Effectiveness of a Clay Pelvic Model: A Hands-on Approach to Understanding Pelvic Floor Anatomy. Issue 1 (7th July 2022) - Chong, Woojin; Tran, Nhi; Bui, Anthony
Abstract : A clay pelvic model is easy to build and would provide an excellent way of reviewing the major landmarks of pelvic anatomy for obstetrics and gynecology residents. Abstract : BACKGROUND: Understanding pelvic anatomy is an important part of education during obstetrics and gynecology residency. Traditional teaching methods to learn pelvic anatomy have obstacles and are often costly. METHOD: We provide a self-constructed clay pelvic model to aid in the mastery of pelvic anatomy for obstetrics and gynecology residents and to estimate whether building a clay pelvic model would increase residents' confidence and knowledge in pelvic anatomy. EXPERIENCE: Each resident constructed a clay pelvic model on a bony pelvis, along with the traditional didactic on pelvic anatomy. Demographics of the participants were obtained, followed by a knowledge test and confidence level and satisfaction surveys. Descriptive analysis and Wilcoxon signed-rank test were used for data analysis. Nine residents (three postgraduate year [PGY]-1, one PGY-2, two PGY-3, three PGY-4) completed the knowledge and confidence questions before and after the simulation, along with the satisfaction survey. The median score from the 10 multiple-choice knowledge questions was 50% (30–70%) on the pretest and 70% (40–100%) on the posttest ( P= not significant). Although most residents scored higher on the posttest, two residents scored 10% lower. Overall, 66.7% of residents improved their knowledge scores up to 30% after the simulation session. Self-assessed confidence level scores improved from 2–3 to 4 (1, lowest; 5, highest) for all questions asked ( P= .010 to approximately .019). A majority of residents responded with 4 or 5 to the satisfaction statements. CONCLUSION: A low-budget clay pelvic model is easy to build and did increase residents' confidence in pelvic anatomy knowledge and satisfaction. Self-constructing a clay pelvic model would provide an excellent way of reviewing the major landmarks of pelvic anatomy.